The Important Functions of Intellectual Capital for Improving the Professionalism Bank Indonesia Employees - Soehari, Tjiptogoro Dinarjo; Budiningsih, Iffah; Tarmizi, Akhmad; Anggiani, Sarfilianty (Advances in Social Sciences Research Journal, 2022)
The purpose of the study was to determine the important functions of Intellectual Capital, which consists of Human Capital (HC), Social capital (SC), and Organizational Capital (OC) in improving the Professionalism of Bank Indonesia Employees. The research method used is a quantitative explorative technique using SPSS IBM 25 with the dependent variable Professionalism (PF) while the independent variables are Human Capital (HC), Social Capital (SC), Organizational Capital (OC) case study conducted at Bank Indonesia with a target population of personnel Experienced in serving at least First Line Officers at Bank Indonesia, namely at least once served as Manager, with a minimum education of Diploma, with work experience above 15 years, an affordable population/target of 140 respondents, with a purposive quota sample that meets the requirements of expert practitioners, 51 respondents. The results obtained: 1) PF = 0.592 + 0.398 HC + 0.460 SC + 0.009 OC. Adjusted R-Sq = 0.704, R-Square = 0.732, F = 40.721 with Sig = 0.000 <0.05. 2) Human Capital and Social Capital (SC) have a significant effect on strengthening Professionalism 3) Organizational Capital has no significant effect on strengthening Professionalism 4) If you ignore Human Capital (HC), Social Capital, and Organizational Capital, then Professionalism is very bad with a constant value of 0.592 at scale 5.